1994
DOI: 10.1103/physrevb.49.8132
|View full text |Cite
|
Sign up to set email alerts
|

Optical absorption of pseudomorphic Si/Ge superlattices

Abstract: The optical properties of pseudomorphic (defect-free) (Si)"/(Ge)"strained-layer superlattices grown on Si, Ge"(001) substrates are studied within the framework of the empirical tight-binding method.Attention is focused on the nature (direct/indirect) of the fundamental energy gap and on the effects of the superlattice periodicity on the optical absorption near the band edge. The band-edge absorption is the main distinguishing feature among different superlattices. It is found that the behavior of the absorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…As discussed previously, the ETB theory rests entirely on a formulation in terms of Hamiltonian matrix elements. This has led researchers to treat the perturbation induced by an electromagnetic field by introducing new parameters to account for additional momentum/dipole matrix elements; see, for example, [157][158][159][160]. Quite recently, however, a new theory has been developed to incorporate time-dependent electromagnetic fields in ETB in a way that is manifestly gauge invariant, guarantees charge conservation and does not introduce any extra free parameters [143,161,162].…”
Section: Optical Propertiesmentioning
confidence: 99%
“…As discussed previously, the ETB theory rests entirely on a formulation in terms of Hamiltonian matrix elements. This has led researchers to treat the perturbation induced by an electromagnetic field by introducing new parameters to account for additional momentum/dipole matrix elements; see, for example, [157][158][159][160]. Quite recently, however, a new theory has been developed to incorporate time-dependent electromagnetic fields in ETB in a way that is manifestly gauge invariant, guarantees charge conservation and does not introduce any extra free parameters [143,161,162].…”
Section: Optical Propertiesmentioning
confidence: 99%
“…5,[14][15][16] This manipulation at the nanometer scale demonstrated that Si/Ge SLs are efficient light-emitting semiconductors. 6,7,10,13,[17][18][19][20] Moreover, these systems have also a great potential in nonlinear optics for technological photonic applications and second-order optical response (χ (2) ) studies have been carried on since the 1990s. 8,9,11,12,[19][20][21][22][23][24][25][26] All these studies were mainly focused on optical second-harmonic generation (SHG) which has finally matured into a powerful technique for probing the electronic and structural properties of materials.…”
mentioning
confidence: 99%
“…6,7,10,13,[17][18][19][20] Moreover, these systems have also a great potential in nonlinear optics for technological photonic applications and second-order optical response (χ (2) ) studies have been carried on since the 1990s. 8,9,11,12,[19][20][21][22][23][24][25][26] All these studies were mainly focused on optical second-harmonic generation (SHG) which has finally matured into a powerful technique for probing the electronic and structural properties of materials. [27][28][29][30] In fact, this nonlinear optical spectroscopy brought a significant progress in manipulating materials thanks to its sensitivity to defects, steps, strain, roughness, and chemical modification.…”
mentioning
confidence: 99%
“…Si/Ge are of interest because of the particular properties they can assume in a superlattice structure. Actually, Because of quantum confinement it is possible to design the band dispersion close to the energy gap obtaining interesting electronic, optical and thermal-conductivity properties [190][191][192][193] Within the optical studies, also the nonlinear SHG process has been experimentally investigated [91,92,[194][195][196][197][198]. In particular, considering the superposition of an equal amount of Si and Ge, if n (i.e., the number of Si and Ge layers) is even the crystal is centrosymmetric and the SHG signal vanishes, while for odd periodicity the nonlinear response is allowed and constructive interference among the periodic interfaces should give an intense harmonic radiation as theoretically predicted [21,199,200].…”
Section: Future Developmentsmentioning
confidence: 99%